Analysis and assessment of the achieved level of servitization in the selected chemical company – Case study - Vlčková, Vladimíra; Podškubková, Lucie (University of Pardubice, 2020)
Manufacturing companies on the B2B market are nowadays focussing more and more on servitization. Globally, 38 % of manufacturing companies have already approached it. Focusing on servitization may be advantageous for manufacturing companies because the area of services is more profitable than the area of products, and it provides more opportunities for growth. Services are also becoming a tool-facilitating sale of products, increasing the customer loyalty, and allowing companies to respond to the growing customer demands. In addition, for chemical companies in the Czech Republic, servitization represents a new opportunity of how to generate a competitive advantage; particularly, towards competitors from the South-East Asia region. Therefore, this paper first aims to assess, based on the literature search, the possibilities and concepts of new service-oriented business models in the chemical industry. Then, based on a case study, it is going to demonstrate the current servitization concept applied by a selected chemical company, perception of its importance, and potential for the future by the sales department staff.
Keywords: services; servitization; company of chemical industry; sales department